HUMIC ACID ADSORPTION BY BATCH METHOD USING MAGNETITE- HUMIC ACID IMPRINTED POLYMER - Ketut Rai Asmara Dipta, I
Humic acid is one of organic pollutant compounds in water and could form complex with various pollutants including dangerous heavy metals. Currently, there are several methods used to separate humic acid from its solution, including oxidation, coagulation, biodegradation and membrane technology. However, these methods have disadvantages in terms of economy and efficiency. Therefore, it is necessary to find alternative methods which are cheaper and more efficient. In this study, humic acid was separated using the adsorption method by magnetite-molecularly imprinted polymer (MMIP). Synthesis of Fe3O4 was carried out using the coprecipitation method with a mole ratio of FeCl3.6H2O and FeSO4.7H2O is 2:1 and addition of NH3 25%. Fe3O4@SiO2 was synthesized using the synthesized Fe3O4 and reacted with tetraethyl orthosilicate. MMIP was synthesized from divinylbenzene, ethylenglycol dimethacrylate, and humic acid as templates. Characterization of synthesized materials and polymers was carried out using Fourier Transform Infrared (FTIR) analysis, X-Ray Diffraction (XRD), and Scanning Electron Microspcope-Energy Dispersive X-Ray Spectroscopy (SEM- EDX). From the results of the IR analysis, it can be seen that Fe3O4 has 2 absorption peaks at 1124.5 cm-1 and 586.3 cm-1. The IR spectrum of Fe3O4@SiO2 has a dominant peak at 1097.5 cm-1 (O-Si-O bond), 583.7 cm-1, 468.7 cm-1, which indicates that the silica layer has formed on the magnetit’s surface. The typical spectrum of MMIP appears at the absorption peaks at 956.53 cm-1, 1152.7 cm-1, 1670.7 cm-1, 1733 cm-1, and 2950 cm-1. From the results of XRD analysis, it was found that the crystallinity of Fe3O4 and Fe3O4@SiO2 was 25.30% and 24.67%, respectively, with the dominant growth area at (311). From the EDS results, it was found that Fe3O4 has a composition of 39.36% Fe and 60.64% O while Fe3O4@2 has a percentage composition of 11.27% Fe, 73.83% O, and 14.09% Si. The solvent suitable for the release of humic acid from the polymer is 2 M NaOH with a desorption percentage of 101.42%.